The Role of Standard and Supplementary Observers in Accurate Illuminance measurements - Listowski, Maciej (Photonics Letters of Poland, 2024)
Typically the sensitivity V2 (λ) for a 2° standard observer is used at photometric measurments. Nevertheless, the light reach the human eye from wider field of view. This fact motivated the International Commission on Illumination to introduce the 10° supplementary observer with sensitivity V10 (λ). This paper analyzes the impact of transition from V2 (λ) to V10 (λ) on measured pc-LEDs illuminance values. The results indicate that the maximum difference is 2% for 3000 K pc-LEDs, 4% for 4000 K pc-LEDs, and 6% for 6500 K pc LEDs. Full Text: PDF References K.S. Gibson, E.P.T. Tyndall, "Visibility of Radiant Energy", Scientific Papers of the Bureau of Standards, 19, 131 (1923). CrossRef E.P. Hyde, W.E. Forsythe, F.E. Cady, J. Frank. "The visibility of radiation", Inst. 185, 829 (1918). CrossRef I. Fryc, M. Listowski, R. Supronowicz, "Going beyond the 20th century color space to evaluate LED color consistency", Opt. Express 31(23), 38666 (2023). CrossRef R. Supronowicz, J. Fan, M. Listowski, A. Watras, I. Fryc, "Application of different metrics for describing light color quality of white LED", Photonics Lett. Pol 13, 32 (2021). CrossRef W.S. Stiles, J.M. Burch, "N.P.L. Colour-matching Investigation: Final Report (1958)", Optica Acta: Int. J. Opt. 6, 1 (1959). CrossRef CIE 165:2005 CIE 10 Degree Photopic Photometric Observer, (2005). DirectLink J. Nathans, D. Thomas, D.S. Hogness, "Molecular Genetics of Human Color Vision: The Genes Encoding Blue, Green, and Red Pigments", Science 232, 193 (1986). CrossRef A. Roorda, A.B. Metha, P. Lennie, D.R. Williams, "Packing arrangement of the three cone classes in primate retina", Vis. Res. 41, 1291 (2001). CrossRef H. Hofer, J. Carroll, J. Neitz, M. Neitz, D.R. Williams, "Organization of the Human Trichromatic Cone Mosaic", J. Neurosci. 25, 9669 (2005). CrossRef C.A. Curcio, K.R. Sloan, R.E. Kalina, A.E. Hendrickson, "Human photoreceptor topography", J. Comp. Neurol. 292, 497 (1990). CrossRef D. Mustafi, A.H. Engel, K. Palczewski, "Structure of cone photoreceptors", Prog. Retin. Eye Res. 28, 289 (2009). CrossRef E.M. Wells-Gray, S.S. Choi, A. Bries, N. Doble, "Variation in rod and cone density from the fovea to the mid-periphery in healthy human retinas using adaptive optics scanning laser ophthalmoscopy", Eye 30, 1135 (2016). CrossRef S. Bara, M.A. Bonmati-Carrion, J.A. Madrid, M.A. Rol, "Multispectral estimation of retinal photoreceptoral inputs", Photonics. Lett. Pol 11, 60 (2019). CrossRef CIE 170-2:2015 Fundamental Chromaticity Diagram With Physiological Axes - Part 2: Spectral Luminous Efficiency Functions And Chromaticity Diagrams, (2015). DirectLink I. Fryc, T. Dimitrova-Grekow, "An automated system for evaluation of the quality of light sources", 2016 IEEE Lighting Conference of the Visegrad Countries (Lumen V4) (2016). CrossRef I. Fryc, "Spectral correction of a detector used in illuminance measurements", Proc. SPIE 3820, 343 (1999). CrossRef H. Wright, C.L. Sanders, D. Gignac, "Design of Glass Filter Combinations for Photometers", Appl. Opt. 8, 2449 (1969). CrossRef S. Winter, D. Lindner, A. Sperling, G. Sauter, S. Brown, T. Larason, Y. Zong, Y. Ohno, Proceedings of the 9th International Conference on New Developments and Applications in Optical Radiometry (NEWRAD), Davos, 2005. DirectLink I. Fryc, P. Tabaka, "The influence of different photometric observers on luxmeter accuracy for LEDs and FLs lamps measurements", Opt. Appl. XLIX, 345 (2019). CrossRef U.S. Energy Information Administration, Commercial Buildings Energy Consumption Survey (2021). DirectLink United Nations Environment Programme (2013). Minamata convention on mercury: text and annexes, (2013). DirectLink M. Listowski, R. Supronowicz, "Color quality consideration when switching from FL to LED", Photonics Lett.Pol. 14, 56 (2022). CrossRef J. Cho, J.H. Park, J.K. Kim, E.F. Schubert, "White light-emitting diodes: History, progress, and future", Phot. Rev. 11, 1600147 (2017). CrossRef K. Bando, K. Sakano, Y. Noguchi, Y. Shimizu, "Development of High-bright and Pure-white LED Lamps", J. Light & Vis. Env. 22, 2 (1998). CrossRef M. Listowski, "Porównanie modelowanych oraz rzeczywistych wartości parametrów świetlnych i kolorymetrycznych białych diod LED pracujących w szerokim zakresie temperatur", Przegląd Elektrotechniczny 1, 59 (2022). CrossRef W. Song, D. Durmus, "Evaluating Energy Efficiency and Colorimetric Quality of Electric Light Sources Using Alternative Spectral Sensitivity Functions", Buildings 12, 2220 (2022). CrossRef S. Jost, A. Thorseth, T. Poikonen, P. Blattner, T. Gerloff, A. Kokka, P. Dekker, M. Smid, A. Ferrero, T. Kubarsepp, P. Gal, S. Källberg, A. Klej, G. Brida, T. Reiners, K. Ludwig, M. Schneider, L. Hui, EMPIR 15SIB07 PhotoLED - Database of LED product spectra, (2021) CrossRef M. Royer, Real Light Source SPDs and Color Data for Use in Research, (2023). CrossRef ANSI C78.377 Electric Lamps - Specifications For The Chromaticity Of Solid-State Lighting Products, (2017). CrossRef Y. Ohno, "Practical Use and Calculation of CCT and Duv", LEUKOS 10(1), 47 (2014). CrossRef